A nanocrystalline tungsten oxide electrochromic coating with excellent cycling stability prepared via a complexation-assisted sol–gel method. Issue 34 (15th August 2016) - Zhou, Dan; Che, Boyang; Kong, Junhua; Lu, Xuehong
Abstract : A nanocrystalline WO3 coating is prepared using a complexation-assisted sol–gel method and exhibits enhanced electrochromic properties, especially excellent electrochemical cycling stability. Abstract : In order to enhance the electrochromic performance of sol–gel derived WO3 coatings, especially the electrochemical cycling stability, a small amount of dopamine (DA) is introduced into a peroxotungstic acid (PTA) precursor sol to form complexes with tungsten on the surface of PTA colloidal nanoparticles. The DA molecules act as a precursor stabilizer, giving the sol a very long shelf life, which is crucial for practical applications, and also play the role of a structure-directing agent, providing a nanocrystal-embedded amorphous WO3 coating by annealing at 300 °C. Compared with the corresponding neat WO3 coating, the modified WO3 coating prepared from the complex sol gives much higher optical contrast, a faster switching speed and a higher coloration efficiency. It also shows excellent long-term cycling stability (maintaining a stable high contrast up to 35 000 cycles), which is far superior to not only the reference neat WO3 coating but also WO3 coatings prepared via other wet chemical routes. The excellent cycling stability may be attributed to the buffering effect of the nanocrystal-embedded amorphous regions, which accommodate the volume change of the nanocrystals induced by ion insertion/extraction. The uniform distribution of the nanometer-sized amorphous and crystal regions may help to reduce stress concentration and hence suppress erosion caused by local stress.